Implementation Of Legal Protections Of Geographical Indications Of Lampung Robusta Coffee In Improving The Economy Of West Lampung Coffee Farmers - Erlina B (Faculty of Law, Universitas Pekalongan, 2023)
West Lampung Regency is one of the Robusta coffee producing areas. Lampung Robusta Coffee is registered by obtaining a Geographical Indication Certificate Number: ID G 000000026 dated May 13, 2014. The problems in this study are a) How is the implementation of legal protection for Lampung Robusta coffee geographical indications in improving the economy of West Lampung coffee farmers and b) What are the factors What are the obstacles in implementing legal protection for Lampung Robusta coffee geographical indications in improving the economy of West Lampung coffee farmers? The research method used is juridical normative and juridical empirical. The conclusion of this study is the implementation of legal protection for Lampung Robusta coffee geographical indications in improving the economy of West Lampung coffee farmers is to provide preventive and repressive forms of protection with reference to the theory of Intellectual Property Rights Robert M. Sherwood. The constraining factors in the implementation of legal protection for Lampung Robusta coffee geographical indications in improving the economy of West Lampung coffee farmers are the low level of public education, the lack of awareness of coffee farmers in West Lampung Regency in including West Lampung Robusta Coffee Geographical Indications in product design, the absence of regulations at the level The Government of West Lampung Regency in implementing the inclusion of Geographical Indications for West Lampung Robusta Coffee and the weak legal awareness of the community towards the importance of Geographical Indications